2020
DOI: 10.1002/sdtp.13877
|View full text |Cite
|
Sign up to set email alerts
|

24‐4: Distinguished Paper: High Refresh Rate and Low Power Consumption AMOLED Panel Using Top‐gate n‐Oxide and p‐LTPS TFTs

Abstract: A Pixel Circuit and a Gate Driver on Array for light-emitting display are presented. By simultaneously utilizing Top-Gate n-type Oxide and p-type LTPS TFTs, the circuits provide high refresh rate and low power consumption. An AMOLED panel with proposed circuits is fabricated and driving at various refresh rate ranging from 1Hz to 120Hz could be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Finally, we design the layout for the proposed pixel using the LTPO TFT process [17], [21], [25][26]. Fig.…”
Section: Pixel Layout and Fabrication Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we design the layout for the proposed pixel using the LTPO TFT process [17], [21], [25][26]. Fig.…”
Section: Pixel Layout and Fabrication Resultsmentioning
confidence: 99%
“…For comparison purpose, the conventional PCVP LTPO AMOLED pixel circuit proposed by Sharp [21] is also shown in Fig. 1(b), which has two n-type oxide TFTs (T03 and T05), five p-type LTPS TFTs (T01-T02, T04, and T06-T07) and one storage capacitor C01.…”
Section: Proposed Pixel Circuit and Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…pixel circuits, scan drivers, emission control drivers needed for refresh, and hold image data) has received less attention. However, more recently, optimizing driving power consumption in AMOLEDs is recently attracting more attention [4][5], with new developments such as reducing display refresh rates without a perceivable flicker by combining low temperature poly-silicon (LTPS) transistors with metal oxide transistors, so-called LTPO technologies. The pivot of engineering focus is due to the increasing impact of driving power consumption, PDriving, to the overall display power consumption, PDisplay.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the operation of the pixel circuit needs scan signals (n type or p type signal with certain pulse width) to enable compensation and data writing for each row and emission (EM) signal to turn corresponding OLED device off during compensation and data writing period, and after that the emission signal controls the OLED device on and emit light. [1] To modulate low gray-scale brightness, the emission signal in some display cases should be a pulse-width-modulated (PWM) one, which could adjust the panel's emission duration [2,3] .…”
Section: Introductionmentioning
confidence: 99%